Understanding the Nazi Genocide Marxism After Auschwitz. - Traverso, Enzo (IIRE (International Institute for Research and Education), 2018)
Enzo Traverso's Understanding the Nazi Genocide draws on the critical and heretical Marxism of Walter Benjamin and the Frankfurt School.